Bank Loan Contract (Journal of actual problems of jurisprudence, 2018)
The importance of bank loan agreement is undeniable, given the popularity and definitely the market nature of this type of contract. The article deals with the provisions of the Civil Code of the Republic of Kazakhstan in terms of the above mentioned loan agreement. The purpose of the study is to define of the validity and completeness of the standards, governing the legal relations of these contract types. Including provisions of the Code are considered in the current practice of the banking credit products, as well as individual requirements of normative legal acts of the market regulator. Generic characteristics of the bank loan contract are determined in the work. According to the research made certain conclusions, including proposals for changes in banking legislation.Key words: bank loan agreement, contract of bank debt, the loan agreement,the bank loan operation, banking.